Report on the results of the 18th International Symposium «Minimally Invasive and Instrumental Spine Surgery», held on the basis of «Sytenko Institute of Spine and Joint pathology, NАS of Ukraine» under the auspices of NASS and SICOT - Fedotova, Inga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article summarizes the results of the 18th International Symposium "Minimally Invasive and Instrumental Spine Surgery", held on the basis of the Institute of Spine and Joint Pathology. prof. MI Sytenko NAMS of Ukraine "under the auspices of ISMISS with the assistance of NASS and SICOT December 5, 2020.